School staff perceptions of mental health among elementary students: A qualitative study in the Kingdom of Saudi Arabia. Issue 4 (2nd October 2022) - Aggad, Roaa; Hennink, Monique; McNabb, Scott J. N.
ABSTRACT: Mental health issues among school-age children are variable yet consistently prevalent worldwide; the implications can be debilitating and long-lasting. Due to their regular interactions with students, school staff members are well poised to identify issues and implement in-school mental health interventions. In this qualitative study, we examine how staff in public elementary schools in Jeddah, Saudi Arabia perceived, assessed, and responded to mental health challenges among their students. We conducted semi-structured interviews with school staff members (n = 16) including teachers (n = 8), counselors (n = 4), and principals (n = 4) from public elementary all-female schools. Using a thematic analysis, we outlined the school staff's perceptions of the causes and identifiers of students' mental health problems, their approach to managing students with mental health problems, and the perceived barriers to improving students' mental health with suggested solutions. Public health implications and future recommendations were discussed.